IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD NEGERI 076 KAYU JATI PANYABUNGAN - Rizki Akbar Sitimpul; Rahmi Seri Hanida; Rica Umrina Lubis (Al-mujahidah, 2026)
This study aims to reveal and describe the implementation of differentiated learning in the Pancasila Education subject for fourth-grade students at SD Negeri 076 Kayu Jati Panyabungan, as well as to identify the supporting and inhibiting factors of its implementation. The background of this research is based on the relatively optimal implementation of Pancasila Education learning, which is influenced by students’ high interest in learning, the use of various instructional strategies, and engaging learning media that encourage students’ active participation. Differentiated learning is considered a relevant strategy as it adapts to students’ individual needs and characteristics. This research employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with the Pancasila Education teacher and the principal, and documentation of classroom activities. The results show that the implementation of differentiated learning consists of three stages: (1) the planning stage, in which the teacher acts as a facilitator and motivator; (2) the implementation stage, which includes diagnostic assessment, differentiation of content, process, and product; and (3) the evaluation stage, involving formative and summative assessments. Supporting factors include a flexible curriculum, student diversity, adequate facilities, government policies and support, and competent teachers. Meanwhile, inhibiting factors include limited time, classroom space, library resources, projectors, and insufficient government training on the Independent Curriculum.